Ultrastructure of the cell surface cellulosome of Clostridium thermocellum and its interaction with cellulose. - Bayer, E A (1986)
The ultrastructural distribution of the cellulosome (a cellulose-binding, multicellulase-containing protein complex) on the cell surface of Clostridium thermocellum YS was examined by cytochemical techniques and immunoelectron microscopy. When cells of the bacterium were grown on cellobiose, cellulosome complexes were compacted into quiescent exocellular protuberant structures. However, when the same cells were grown on cellulose, these polycellulosomal organelles underwent extensive structural transformation; after attachment to the insoluble substrate, the protuberances protracted rapidly to form fibrous "contact corridors." The contact zones mediated physically between the cellulosome (which was intimately attached to the cellulose matrix) and the bacterial cell surface (which was otherwise detached from its substrate). In addition, cell-free cellulosome clusters coated the surface of the cellulose substrate. The cellulose-bound cellulosome clusters appear to be the site of active cellulolysis, the products of which are conveyed subsequently to the cell surface via the exocellular contact zones.